Analysis of Stability, Rheological and Structural Properties of Oleogels Obtained from Peanut Oil Structured with Yellow Beeswax - Anna Zbikowska; Sylwia Onacik-Gür; Małgorzata Kowalska; Michał Sowiński; Iwona Szymańska; Katarzyna Żbikowska; Katarzyna Marciniak-Łukasiak; Wojciech Werpachowski (Gels, 2022)
The aim of this study was to evaluate the macro- and microscopic properties of oleogels with yellow beeswax using different methods, especially modern optical techniques. Microrheological properties, physical stability and morphology of oleogel crystals obtained by structuring of peanut oil with yellow beeswax was analyzed. It was observed that oleogels, even with the smallest concentration of beeswax (2%), were resistant to centrifugal force. Increase in yellow beeswax concentration (from 2, 4, 6 to 8 %) resulted in significant differences in the characteristics of oleogels: increased elasticity (EI), macroscopic viscosity (MVI) and the firmness values of oleogels. It was concluded that non-invasive optical techniques (multi-speckle diffusing wave spectroscopy—Rheolaser Master) are useful in obtaining a quick evaluation of physical properties of oleogels at the microstructural level, and the received information allows for quality assessment.